INTERRELATION BETWEEN CARDIOVASCULAR RISK FACTORS AND TELOMERE BIOLOGY WITH THE SIGNS OF VASCULAR AGING - A. S. Kruglikova; I. D. Strajesko; O. N. Tkacheva; D. U. Akasheva; E. V. Plokhova; V. S. Pykhtina; E. V. Dudinskaya; O. Yu. Isaykina; N. V. Sharashkina; I. N. Ozerova; V. A. Vygodin; N. V. Gomyranova (Кардиоваскулярная терапия и профилактика)
Aim. To study interrelationship between cardiovascular risk factors and cellular and vascular aging processes. Material and methods. Totally 136 patients were included having no signs of cardiovascular diseases, diabetes 2nd type and receiving no drug therapy, but with one or several risk factors for cardiovascular diseases (smoking, arterial hypertension, obesity, dyslipidemia, fasting hyperglycemia). The telomere length and telomerase activity was measured by polymerase chain reaction. The thickness of intima-media complex (TIMC) and presence of atherosclerotic plaques (ASP) were measured by duplex scanning of right and left carotid arteries. Pulse wave velocity (PWV) was measured by applanation tonometry. Biochemical tests done by standard.Results. PWV significantly correlated with age, body mass index, glycosilated hemoglobin level, fasting glycemia and telomere length. Presence of ASP and increased TIMC significantly correlated with age, body mass index, arterial hypertension, dyslipidemia. Conclusion. Increase of arterial wall stiffness and subclinical atherosclerotic disease have different causes. The level of PWV more linked with carbohydrate metabolism disorder, and TIMC and ASP are linked with lipid disorders.